London dispersion as important factor for the stabilization of (Z)-azobenzenes in the presence of hydrogen bonding - Heindl, Andreas H.; Wende, Raffael C.; Wegner, Hermann A. (Beilstein Journal of Organic Chemistry, 2018)
The understanding and control of the light-induced isomerization of azobenzenes as one of the most important classes of molecular switches is crucial for the design of light-responsive materials using this entity. Herein, we present the stabilization of metastable (Z)-azobenzenes by London dispersion interactions, even in the presence of comparably stronger hydrogen bonds in various solvents. The Z→E isomerization rates of several N-substituted 4,4′-bis(4-aminobenzyl)azobenzenes were measured. An intramolecular stabilization was observed and explained by the interplay of intramolecular amide and carbamate hydrogen bonds as well as London dispersion interactions. Whereas in toluene, 1,4-dioxane and tert-butyl methyl ether the hydrogen bonds dominate, the variation in stabilization of the different substituted azobenzenes in dimethyl sulfoxide can be rationalized by London dispersion interactions. These findings were supported by conformational analysis and DFT computations and reveal low-energy London dispersion forces to be a significant factor, even in the presence of hydrogen bonds.
Keywords: azobenzene; hydrogen bonding; London dispersion; molecular switches

(untitled) - Hartley, G. S. (Nature, 1937)

(untitled) - Velema, W. A.; Szymanski, W.; Feringa, B. L. (J. Am. Chem. Soc., 2014)

(untitled) - Broichhagen, J.; Trauner, D. (Curr. Opin. Chem. Biol., 2014)

(untitled) - Van der Berg, J. P.; Velema, W. A.; Szymanski, W.; Driessen, A. J. M.; Feringa, B. L. (Chem. Sci., 2015)

(untitled) - Bellotto, S.; Chen, S.; Rentero Rebollo, I.; Wegner, H. A.; Heinis, C. (J. Am. Chem. Soc., 2014)

(untitled) - Schweighauser, L.; Wegner, H. A. (ChemBioChem, 2015)

(untitled) - Merino, E.; Ribagorda, M. (Beilstein J. Org. Chem., 2012)

(untitled) - Heitmann, G.; Schütt, C.; Herges, R. (Eur. J. Org. Chem., 2016)

(untitled) - Pieraccini, S.; Gottarelli, G.; Labruto, R.; Masiero, S.; Pandoli, O.; Spada, G. P. (Chem. – Eur. J., 2004)

(untitled) - Ikeda, T.; Tsutsumi, O. (Science, 1995)

(untitled) - Lennartson, A.; Roffey, A.; Moth-Poulsen, K. (Tetrahedron Lett., 2015)

(untitled) - Merino, E. (Chem. Soc. Rev., 2011)

(untitled) - Griffiths, J. (Chem. Soc. Rev., 1972)

(untitled) - Bandara, H. M. D.; Burdette, S. C. (Chem. Soc. Rev., 2012)

(untitled) - Reuter, R.; Wegner, H. A. (Chem. Commun., 2011)

(untitled) - Norikane, Y.; Katoh, R.; Tamaoki, N. (Chem. Commun., 2008)

(untitled) - Siewertsen, R.; Neumann, H.; Buchheim-Stehn, B.; Herges, R.; Näther, C.; Renth, F.; Temps, F. (J. Am. Chem. Soc., 2009)

(untitled) - Heindl, A. H.; Schweighauser, L.; Logemann, C.; Wegner, H. A. (Synthesis, 2017)

(untitled) - Knie, C.; Utecht, M.; Zhao, F.; Kulla, H.; Kovalenko, S.; Brouwer, A. M.; Saalfrank, P.; Hecht, S.; Bléger, D. (Chem. – Eur. J., 2014)

(untitled) - Goulet-Hanssens, A.; Utecht, M.; Mutruc, D.; Titov, E.; Schwarz, J.; Grubert, L.; Bléger, D.; Saalfrank, P.; Hecht, S. (J. Am. Chem. Soc., 2017)

(untitled) - Wagner, J. P.; Schreiner, P. R. (Angew. Chem., Int. Ed., 2015)

(untitled) - Rösel, S.; Balestrieri, C.; Schreiner, P. R. (Chem. Sci., 2017)

(untitled) - Schweighauser, L.; Strauss, M. A.; Bellotto, S.; Wegner, H. A. (Angew. Chem., Int. Ed., 2015)

(untitled) - Grimme, S.; Huenerbein, R.; Ehrlich, S. (ChemPhysChem, 2011)

(untitled) - Schaefer, T.; Niemczura, W.; Danchura, W.; Wildman, T. A. (Can. J. Chem., 1979)

Gaussian 16, Revision A.03 (Gaussian, Inc., 2016)

(untitled) - Becke, A. D. (J. Chem. Phys., 1993)

(untitled) - Krishnan, R.; Binkley, J. S.; Seeger, R.; Pople, J. A. (J. Chem. Phys., 1980)

(untitled) - Lee, C.; Yang, W.; Parr, R. G. (Phys. Rev. B: Condens. Matter Mater. Phys., 1988)

(untitled) - Grimme, S.; Antony, J.; Ehrlich, S.; Krieg, H. (J. Chem. Phys., 2010)

(untitled) - Grimme, S.; Ehrlich, S.; Goerigk, L. (J. Comput. Chem., 2011)

(untitled) - Johnson, E. R.; Keinan, S.; Mori-Sánchez, P.; Contreras-García, J.; Cohen, A. J.; Yang, W. (J. Am. Chem. Soc., 2010)

(untitled) - Contreras-García, J.; Johnson, E. R.; Keinan, S.; Chaudret, R.; Piquemal, J.-P.; Beratan, D. N.; Yang, W. (J. Chem. Theory Comput., 2011)

(untitled) - Le Questel, J.-Y.; Laurence, C.; Lachkar, A.; Helbert, M.; Berthelot, M. (J. Chem. Soc., Perkin Trans. 2, 1992)

(untitled) - Rospenk, M.; Zeegers-Huyskens, T. (J. Phys. Chem., 1987)

(untitled) - Wende, R. C.; Seitz, A.; Niedek, D.; Schuler, S. M. M.; Hofmann, C.; Becker, J.; Schreiner, P. R. (Angew. Chem., Int. Ed., 2016)

(untitled) - Müller, C. E.; Zell, D.; Hrdina, R.; Wende, R. C.; Wanka, L.; Schuler, S. M. M.; Schreiner, P. R. (J. Org. Chem., 2013)